Bonding Behaviour of Steel and Concrete Containing 10% Palm Oil Fuel Ash (POFA) and Expanded Polystyrene (EPS) - MOHD NASHARUDIN, MOHAMAD ARMIN HAKIMY; Osman, Hairi (Progress in Engineering Application and Technology, 2023)
This study focusses on the application of using Palm Oil Fuel Ash (POFA) and Expanded Polystyrene (EPS) as the replacement materials in concrete. POFA was replaced the cement up to 10% of its mass in the concrete mixture and the fine aggregate was replaced by EPS up to 30% of its volume in the concrete mixture. The mechanical properties of concrete containing EPS and POFA as replacement materials were determined in terms of workability, compressive strength, and bonding performance between steel and concrete. The bonding steel and concrete was then compared with the normal concrete with pull-out testing. Expanded polystyrene granules can be included into a concrete mix to make lightweight polystyrene aggregate concrete with varying densities, compressive strengths, and tensile strengths. As the results, the optimum percentage of replacement of EPS and POFA were determined. The optimum percentage was 10% POFA and 20% EPS for compressive cube test and 10% POFA with 30% EPS for pull-out concrete test as the result were nearly to normal concrete value. In conclusion, POFA consists high percentage of silica that make it a good pozzolanic material to replace cement in concrete mixture.